2014
DOI: 10.1371/journal.ppat.1003829
|View full text |Cite
|
Sign up to set email alerts
|

A Compositional Look at the Human Gastrointestinal Microbiome and Immune Activation Parameters in HIV Infected Subjects

Abstract: HIV progression is characterized by immune activation and microbial translocation. One factor that may be contributing to HIV progression could be a dysbiotic microbiome. We therefore hypothesized that the GI mucosal microbiome is altered in HIV patients and this alteration correlates with immune activation in HIV. 121 specimens were collected from 21 HIV positive and 22 control human subjects during colonoscopy. The composition of the lower gastrointestinal tract mucosal and luminal bacterial microbiome was c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

64
452
20

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 363 publications
(550 citation statements)
references
References 58 publications
64
452
20
Order By: Relevance
“…In chronic HIV infection, an altered gut microbiome is associated with mucosal dysfunction, systemic inflammation, and disease progression (9,10,12,39). FMT is emerging as an effective treatment option for antibiotic-refractory intestinal infections, such as C. difficile infections, as well as for chronic inflammatory conditions of the gut that are known to be associated with dysbiosis (24,25,40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In chronic HIV infection, an altered gut microbiome is associated with mucosal dysfunction, systemic inflammation, and disease progression (9,10,12,39). FMT is emerging as an effective treatment option for antibiotic-refractory intestinal infections, such as C. difficile infections, as well as for chronic inflammatory conditions of the gut that are known to be associated with dysbiosis (24,25,40).…”
Section: Discussionmentioning
confidence: 99%
“…This is typically characterized by an overall loss of diversity, with alterations to the phyla Bacteroidetes, Firmicutes, and Proteobacteria (11). Specifically, the loss of beneficial bacterial genera, such as Bacteroides, Lactobacillus, and Bifidobacterium, has been observed and associated with pathogenesis (9,10,12,13). Furthermore, the levels of several pathogenic Proteobacteria have been observed to increase during HIV infection, including those within the genera Campylobacter, Escherichia, Acinetobacter, Desulfovibrio, and Pseudomonas, as have those of Prevotella species (9)(10)(11).…”
mentioning
confidence: 99%
“…Results from a study by Gaardbo et al showed that microberelated effects in the gut are associated with CD4 T-cell loss during HIV-1 infection (35). The dysbiosis that occurs in the gut of HIV-1-infected subjects persisting on ART describes the imbalance of bacterial diversity that is illustrated by increased proinflammatory pathogenic strains (63,64). Importantly, the enhanced tryptophan metabolism related to the composition of the gut microbiota has been linked to the disease progression contributed by enhanced Kyn production in the gut (65).…”
Section: Ccr7mentioning
confidence: 99%
“…An altered gastrointestinal microbiome appears to occur early in the course of HIV-infection and may contribute to, or is at least correlated with, mucosal inflammatory activity, mucosal CD4 + T-cell depletion, and peripheral CD8 + T-cell activation [39][40][41]. The microbiome alterations and accompanying local and systemic immune effects persist following the early stages of infection and do not revert with ART, possibly because of a persistent presence of HIV at the mucosal surface or the lasting depletion of gastrointestinal CD4 + T cells and other immune effectors despite effective suppression of plasma viremia [42,43]. In a study of rectosigmoid biopsy specimens from HIVinfected subjects not yet receiving ART, ART recipients, and HIV-negative controls, those with untreated HIV infection were found to have a marked dysbiosis of mucosal-adherent bacteria characterized by increased Proteobacteria levels and reduced Bacteroidetes levels, which was accompanied by increased mucosal CD4 + and CD8 + T-cell activation, increased circulating CD8 + T-cell activation, and, among ART recipients, increased circulating interleukin 6 (IL-6) levels [44].…”
Section: Malnutrition Hiv and The Microbiomementioning
confidence: 99%